Analisis Yuridis Putusan Pemidanaan Dalam Tindak Pidana Pencabulan Dengan Korban Anak Dibawah Umur (Putusan Nomor 65/Pid.Sus/2023/PN Klb) - Saputra, Elton Krisna; Guntari , Titiek (PT Elaborium Elevasi Indonesia, 2025)
Sexual abuse of minors is a serious crime often committed by adults against vulnerable children. This case highlights the importance of applying the law not only to punish the offender but also to protect the rights of children as victims. This study aims to analyze the legal application in the case of Decision No. 65/Pid.Sus/2023/PN Klb, which tried Marthen Lakau, a Civil Servant who committed sexual abuse against five minors. Using a normative legal method and document analysis, the study evaluates the judge’s considerations that reflect principles of justice and child protection. The research findings indicate that the sentence imposed on the defendant, which includes 15 years of imprisonment and a fine, aims to provide deterrence and protect society. However, the study also emphasizes the importance of psychological protection for the victims and rehabilitation for the perpetrator to prevent future occurrences of similar crimes.